2022
DOI: 10.1002/wat2.1611
|View full text |Cite
|
Sign up to set email alerts
|

Extreme precipitation events

Abstract: The effect of increased populations concentrated in urban areas, coupled with the ongoing threat of climate change, means that society is becoming increasingly vulnerable to the effects of extreme precipitation. The study of these events is therefore a key topic in climate research, in their physical basis, in the study of their impacts, and in our adaptation to them. From a meteorological perspective, the main questions are related to the definition of extreme events, changes in their distribution and intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 174 publications
0
20
0
Order By: Relevance
“…In contrast, there was no positive solar radiation anomaly in July 2020, and the SIC reduced to about 50% at the end of July. Park et al (2015), Lee et al (2017) and Gimeno et al (2019) found that moisture from low latitudes, rather than local water vapor, is the main cause of abnormal LWN (Park, Lee, Son, Feldstein, and Kosaka, 2015;Lee, Kwon, Yeh, Kwon, Park, Park et al, 2017;Gimeno, Vázquez, Eiras-Barca, Sorí, Algarra, and Nieto, 2019). In this study, we found that in July 2019, the heat flux (Figure 6A), the water vapor flux (Figure 6C) and the cloud liquid water flux (Figure 6E) in the southern Northwind Ridge all showed strong poleward transport from south to north; whereas in July 2020, the three fluxes had southward transport (Figures 6B,D,F).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, there was no positive solar radiation anomaly in July 2020, and the SIC reduced to about 50% at the end of July. Park et al (2015), Lee et al (2017) and Gimeno et al (2019) found that moisture from low latitudes, rather than local water vapor, is the main cause of abnormal LWN (Park, Lee, Son, Feldstein, and Kosaka, 2015;Lee, Kwon, Yeh, Kwon, Park, Park et al, 2017;Gimeno, Vázquez, Eiras-Barca, Sorí, Algarra, and Nieto, 2019). In this study, we found that in July 2019, the heat flux (Figure 6A), the water vapor flux (Figure 6C) and the cloud liquid water flux (Figure 6E) in the southern Northwind Ridge all showed strong poleward transport from south to north; whereas in July 2020, the three fluxes had southward transport (Figures 6B,D,F).…”
Section: Resultsmentioning
confidence: 96%
“…Compared with 2020, the strengthening of the warm and humid advection from the low latitudes at the southern Northwind Ridge in July 2019 was mainly caused by an abnormal pressure field, which can excite anomalous winds (Wei, Qin, and Li, 2017;Gimeno, Vázquez, Eiras-Barca, Sorí, Algarra, and Nieto, 2019). On the MSLP field (Figure 6 and Supplementary Figure S6), the centers of low MSLP and high Frontiers in Earth Science frontiersin.org Frontiers in Earth Science frontiersin.org 08 MSLP in the Arctic Ocean intersected near 84 °N in July 2019.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Changes in precipitation extremes and characteristics at both regional and global scales due to climate change and variability need to be investigated [3,4]. Various characteristics of precipitation have been studied in relation to ongoing climate change, such as precipitation amounts, intensity, and extremes [5][6][7]. In the context of extremes events of precipitation, the annual maximum daily rainfall (Pmax) is defined as an important key [8,9] for intensity-duration-frequency events [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years with growing concerns about environmental degradation and about soil water conservation, the interest in Pmax standards is growing, since several methodologies and applications depend on Pmax, such as studies of intensity-durationfrequency, daily rainfall disaggregation, water resources planning, design, and management [7,10,12,13]. Trend analysis has proved to be a useful tool for these applications since trend detection of hydrological variables such as streamflow and precipitation provides useful information on the possibility of changing the trend of variables in the future [4,12,14].…”
Section: Introductionmentioning
confidence: 99%